Study Iron Homeostasis of Infected and Non-Infected Iraqi Camels with Trypanosomiasis - Al-Rubaie, Laith S.G.; Al-Qayim, Majida A.J.; Al-Rubaie, Haider M. A.; Y., Al-badrawi A. (The Iraqi Journal of Veterinary Medicine, 2020)
Trypanosomiasis is one of the common parasitic diseases, which infects the dromedary camels and decreases the numbers of these animals in Iraq. To get the best knowledge of the changes of iron status in camels infected with trypanosomiasis, in an attempt to take advantage of these variables as markers for infection, we designed this study. The current study conducted in blood sample collection from155 dromedary camels, 33 were infected (21.29%), according to the status of infection with Trypanosoma evansi that depends on blood smear examination as a golden test. Results denote significant differences of infection ratio by sex and age, from total of 132 male tested, 29 (21.96%) infected, distributed into 12 (%41.37) of age ≤ 2 years and 17 (58.62) of ≥ 2 years. From 23 female tested, 4 (17.39%) were infected at age ≤ 2 years. Furthermore, the results of this study demonstrated significant (p˂0.05) decrease in total serum iron, transferrin saturation, ferritin, whereas increased in total iron binding capacity and unsaturated iron binding capacity in the infected male and female camels with different age. Analyzed data of iron status parameters denoted that the cutoff point test between sensitivity (97) and specificity (100) for serum iron is (≤67.26), for transferrin saturation is (≤17.23) between the sensitivity and specificity (100) and (≥378.66), for total iron binding capacity between the sensitivity and specificity (93.9 and 96.7) respectively. Also, the cutoff point test between the sensitivity (100) and specificity (96.7) for unsaturated iron binding capacity is (≥301.27) and ferritin concentration has a cutoff point is (≤ 249.88) for the sensitivity (100) and specificity (99.2). It could be concluded from what was stated in the results of the current study, that the measurement of the concentration of serum ferritin could be considered as a good marker for the T. evansi infection